Psychoanalyzing cinema a productive encounter with Lacan, Deleuze, and Zizek - Jagodzinski, Jan 1948-. (New York, NY Houndmills, Basingstoke, Hampshire Palgrave Macmillan, 2012)
"Brings together and compares/contrasts the writing/influence of the two most important theorists in film studies today: Gilles Deleuze and Slavoj Zizek. Psychoanalysis and schizoanalysis have provided two very powerful approaches to film and its theorization. While the former approach has certainly held the field in terms of theory, the latter position has emerged as its rival,forcing an encounter that needs to be taken seriously. Where does one approach leave off and the other begin? Is there such a break, or has such a line been 'trumped up' by both sides to hold on to their territories? Are both approaches necessary to one another, recalling that Deleuze and Guattari's criticism of psychoanalysis was basically confined to Freud at first. They were quite satisfied with Lacan's development of objet a, or at least as they wrote about it in Anti-Oedipus. A number of theorists have argued that Deleuze and Guattari have 'simply' continued to articulate the Real. To what extent can objet a and the Deleuzian 'event' be theorized as synonymous or complementary concepts? Is the Lacanian sinthome as applied to film comparable to schizoanalysis of film, and what might that be? This is to say, the late Lacan is much more useful to the question(s) than the Lacan of Screen theory etc. A productive encounter (I am utilizing this grapheme specifically for this encounter) needs to take place to explore the tensions as well as the overlaps that exist between these two approaches. These essays attempt to do just that" Provided by publisher.
Includes bibliographical references.
Keywords: Lacan, Jacques -- 1901-1981 -- Criticism and interpretation; Deleuze, Gilles -- 1925-1995 -- Criticism and interpretation; Zizek, Slavoj -- Criticism and interpretation; Psychoanalysis and motion pictures; Motion pictures -- Psychological aspects